Embodied energy in thermal energy storage (TES) systems for high temperature applications. (1st January 2015) - Miró, Laia; Oró, Eduard; Boer, Dieter; Cabeza, Luisa F.
Highlights: Environmental impact of three high temperature TES systems in solar plants. The embodied energy in the three systems has been quantified and compared. The embodied energy has been calculated using the cumulative energy demand method. The highest total embodied energy is obtained by the TES system using PCM. Abstract: Currently, there is an increasing interest in concentrated solar power (CSP) plants as alternative to produce renewable electricity at large scale by using mirrors to concentrate the solar energy and to convert it into high temperature heat. These facilities can be combined with thermal energy storage (TES) systems, which are, nowadays, one of the most feasible solutions in facing the challenge of the intermittent energy supply and demand. However, they are still in research process and, for that, there is a lack of environmental impact studies of these TES systems complementing solar plants. This paper accounts the environmental impact of three TES systems used nowadays in high temperature applications for CSP plants: first, a system which stores sensible heat in high temperature concrete; second, a system storing sensible heat in molten salts; and third, another system with molten salts but storing latent heat. All the systems are normalised in order to be comparable between them due to its initial storage capacity difference. The environmental impact is accounted by calculating the amount of embodied energy in the components of the different TES systems. Notice that embodied energy refers to the total energy inputs required to make a component. Between the three systems, the sensible heat system using concrete as storage material is the one with less environmental impact while the molten salts and PCM have a higher value of embodied energy, mainly due to the nitrate mixture used as storage material. Finally, advantages and disadvantages of the method proposed used are discussed.